A True Random Number Generator Using Threshold‐Switching‐Based Memristors in an Efficient Circuit Design. (28th November 2018) - Woo, Kyung Seok; Wang, Yongmin; Kim, Jihun; Kim, Yumin; Kwon, Young Jae; Yoon, Jung Ho; Kim, Woohyun; Hwang, Cheol Seong
Abstract: A true random number generator (TRNG) based on the stochastic delay and relaxation times of the threshold switching (TS) behavior in a Pt/HfO2 /TiN memristor is proposed. The stochasticities of this device are attributed to its electron trapping and detrapping processes. This electronic‐switching‐based memristor exhibits several advantages, such as low power consumption and high reliability. A new circuit is designed to improve the simplicity, miniaturization, and lifetime of TRNG. The bitstreams collected from this TRNG pass the National Institute of Standards and Technology randomness tests without postprocessing, verifying the feasibility of adopting the memristor in hardware security applications. The bit generation rate in this work is sufficient for encryption applications requiring low power and low speed. Abstract : A true random number generator (TRNG) based on a threshold switching behavior in a Pt/HfO2 /TiN (PHT) memristor is proposed. The PHT memristor has stochastic delay and relaxation times, which are attributed to electron trapping and detrapping processes. A new circuit is designed to reduce the circuit size and to further improve the TRNG lifetime.